Technology, teaching innovation and taxation for undergraduate digital natives - Francisco J. Delgado Rivero; Roberto Fernández Llera (Universitat Politècnica de València, 2013)
Higher education is immersed in a deep reform for its adjustment to the European Higher Education Area (EHEA), where degrees and competences are validated for the whole European area. In this context, the teaching of taxation in the Degrees of Social and Law Science, as well as the rest of disciplines, goes through a period of reflection and it is starting up a series of experiences to increase the role played by the students in their learning process. In this paper we analyze the task carried out in the course Spanish Public Sector I, directed to last-year-of-a-course economics students. Most of them are digital natives and therefore the task is put into practice through the use of Information and Communication Technologies (ICT) in the Virtual Campus of the University of Oviedo. This experience will help us face this new period adapted to Bologna.